Machiavelli and Tocqueville on War and Armies - Tegos, Spyridon (Conatus - Journal of Philosophy, 2023)
In the Democracy in America’s chapters on war and armies in the transition from the aristocratic to the democratic social state (état social), Tocqueville briefly draws on Machiavelli regarding the conquest of a country with or without intermediary powers between political leadership and the people by which he primarily understands the existence of local nobilities. In this reference, Tocqueville is quick to express skepticism about the overstated importance of Machiavelli in the history of political philosophy. In different places of his work though a more mitigated stance is documented. A comparative approach of Machiavelli and Tocqueville on war may seem odd, even inappropriate. In this paper I argue that the “brief encounter,” in Melvin Richter’s terms, of Tocqueville with Machiavelli can be fruitfully explored in order to make sense of the key importance for modern warfare of the collapse of nobility in Europe. Concomitantly, Machiavelli ‘s intuitions about conquering an absolutist state without intermediary powers compared to a state endowed with “prince” and “barons” can be further elaborated to better grasp its impact on wars including civil strife. In this paper I first explore Machiavelli’s perception of the intermediary powers in conquest and broadly in warfare paying due attention to the importance for the preservation of liberty of latent or open civil discord between social powers or classes; then I turn to Tocqueville’s rich analysis of the transformation of modern warfare due to democratic centralization and obsession with private welfare. Democratic armies constantly challenge democratic liberty and they can sometimes successfully albeit perversely integrate democratic ambition and turn it against democracy. I conclude with some reflections on the connection between war and politics regarding latent civil conflicts in democracies.